Impact of Nano-Fuel Additives and Nano-Lubricant Oil Additives on Diesel Engine Performance and Emission Characteristics - Dipakkumar Chimangiri Gosai; Ashishkumar Jashvantlal Modi; Anil Kumar Gillawat (Journal of Heat and Mass Transfer Research)
Fuel saving and emission control in transportation is a global critical issue, so research is required to concentrate on the energy conservation of diesel engines. Generally, in an internal combustion Engine, around 66 % of the total heat is lost and, around 33% is used for Brake Power. It is very important to improve the energy level of the engine in the field of automobiles, and this will be shown in the heat balance sheet of diesel engines. An attempt has been made to fulfill the above requirement by adding CuO and ZnO nano-additives to pure diesel fuel and Al2O3 and ZnO nano-lubricant additives to SAE 15W-40 engine lubricant oil by sonication process. Experimental work on a vertical twin-cylinder four-stroke, water-cooled, advanced computerized diesel engine was carried out with no load to full load condition using a computerised eddy current dynamometer attachment. The performance of the engine is evaluated by considering specific fuel consumption, brake thermal, mechanical, and volumetric efficiency, and exhaust emission. Results show that Specific fuel consumption is reduced by about 14.98%, Brake thermal efficiency is increased by about 17.62%, and Mechanical efficiency is increased by about 3.94%, respectively, using both nano fuel additives and nano lubricant additives. For exhaust, the emission is reduced by 20.04%, 10.25% for CO and NOx, and increased in CO2 by 29.16%. With the application of nano additives in fuel as well as in lubricating oil, the overall thermal performance can be appreciably improved, and the exhaust gas pollutant from the engine can be significantly reduced.